Dental Treatment Needs in Vancouver Inner-City Elementary School-Aged Children - F. Samim; J. Aleksejuniene; C. Zed; N. Salimi; C. P. Emperumal (International Journal of Dentistry)
Aims. To examine the dental treatment needs of inner-city Vancouver elementary school-aged children and relate them to sociodemographic characteristics. Methods. A census sampling comprising 562 children from six out of eight eligible schools was chosen (response rate was 65.4%). Dental treatment needs were assessed based on criteria from the World Health Organization. Results. Every third child examined needed at least one restorative treatment. A higher proportion of children born outside Canada were in need of more extensive dental treatments such as pulp care and extractions compared to the children born in Canada. There were no statistically significant differences in dental treatment needs between age, gender, or income groups or between children with or without dental insurance (Chi Squared P>0.05). The best significant predictors (Linear Multiple Regression, P>0.05) of higher dental treatment needs were being born outside Canada, gender, time of last dental visit, and family income. Having dental insurance did not associate with needing less treatment. Conclusion. A high level of unmet dental treatment needs (32%) was found in inner-city Vancouver elementary school-aged children. Children born outside Canada, particularly the ones who recently arrived to Canada, needed more extensive dental treatments than children born in Canada.